Making debt relief conditionality pro-poor - Oliver Morrissey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper considers how the conditionality inherent in HIPC debt relief should be constituted to promote pro-poor policies. There are two dimensions to this. First, the extent to which the policies proposed are pro-poor. Second, the potential for releasing resources for pro-poor expenditures. The paper provides an analytical framework to describe the policy environment for poverty reduction, and identifies where donor effort and influence are most likely to be effective. The paper argues that the elements of debt relief conditionality should be tailored to the features of the poverty-reduction policy environment and provides guidelines for the design of conditionality.
Keywords: F35; O19; O55; 330; aid conditionality; HIPC; debt relief; East Africa; Schuldenerlass; Entwicklungshilfekonditionen; Ostafrika; HIPC